2019
DOI: 10.1007/978-3-030-13736-6_7
|View full text |Cite
|
Sign up to set email alerts
|

Intensity Standardization of Skeleton in Follow-Up Whole-Body MRI

Abstract: The value of whole-body MRI is constantly growing and is currently employed in several bone pathologies including diagnosis and prognosis of multiple myeloma, musculoskeletal imaging and evaluation of treatment response assessment in bone metastases. Intra-patient follow-up MR images acquired over time do not only suffer from spatial misalignments caused by change in patient positioning and body composition, but also intensity inhomogeneities, making the absolute MR intensity values inherently non-comparable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Another limitation of the present work is reliance on data from a single institution and scanner manufacturer. To establish calibration across scanners from different manufacturers and accommodate changes in imaging parameters such as field strength and b-values, more sophisticated techniques like histogram matching [24, 25] or the incorporation of machine learning methodologies [26] would be necessary. The present study is instructive, though, as it reveals that even minor variations of 15ms in TE can result in significant differences in quantitative measurements that require careful calibration and demonstrates physics-based correction for these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of the present work is reliance on data from a single institution and scanner manufacturer. To establish calibration across scanners from different manufacturers and accommodate changes in imaging parameters such as field strength and b-values, more sophisticated techniques like histogram matching [24, 25] or the incorporation of machine learning methodologies [26] would be necessary. The present study is instructive, though, as it reveals that even minor variations of 15ms in TE can result in significant differences in quantitative measurements that require careful calibration and demonstrates physics-based correction for these differences.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated initial results in a cohort of 16 patients with advanced prostate cancer (APC) but noted the limitation that protocols must include at least three b-values, which can make the approach difficult to adopt at some centres. Ceranka et al [19] proposed a new method for signal intensity normalisation between baseline and follow-up wholebody MRI. The method involved two steps.…”
Section: Introductionmentioning
confidence: 99%